On the calculation of plates by the series representation of the deflection function - Ahanova, A.S.; Yessenbayeva, G.A.; Tursyngaliev, N.K. (Bulletin of the Karaganda University. Mathematics Series, 2016)
In the article calculations of rectangular plates by the series representation of the deflection function are presented. For the considered rectangular plate the investigation was determined by finding the minimum of the potential energy of the plate by Ritz variation method and by direct substitution of series representation of the deflection function in the equilibrium equation by Bubnov-Galerkin method. To illustrate the above variation method, specific examples of the calculation were given for the square hinged bearing plate and for the rectangle plate rigidly clamped along the whole contour and loaded by the uniformly distributed load of the given intensity.